Effects of integrated watershed management on livestock-water productivity in water scarce areas in Ethiopia - Descheemaeker, Katrien K.; Mapedza, Everisto D.; Amede, Tilahun; Ayalneh, W. (Elsevier, 2010)
In the water scarce Lenche Dima watershed in the northern Ethiopian highlands community based integrated watershed management was implemented to fight land degradation, raise agricultural productivity and improve farmers’ livelihoods. The effects of two interventions, namely exclosures and water harvesting structures, were assessed based on data from farmers’ interviews, measurements of feed biomass production, and estimates of energy production and requirements. Water used for livestock feed production was obtained through simple soil water balance modelling. By protecting 40% of the rangelands, the water productivity of the feed increased by about 20%. This indicated that exclosure establishment could lead to similar improvements in livestock water productivity (LWP, defined as the ratio of livestock benefits over the water used in producing these). Water harvesting structures ensured year-round water availability in the homestead, which resulted in less energy used for walking to drinking points. A considerable amount of energy was thus saved, which could be used for livestock production and improved animal health without additional water use. Besides restoring regulating and supporting ecosystem services, both interventions led to a more efficient use of the scarce water resources for biomass and livestock production.